The implication of stigma on people living with HIV and the role of social support – a case report - Abdul Manap, Abdul Hadi; Lee, Ping Yein; Ismail, Adibah Hanim (Academy of Family Physicians of Malaysia, 2020)
Despite the advancements made in the knowledge and treatment of the human immunodeficiency virus (HIV) since it was first discovered, people living with HIV (PLWH) continue to be stigmatized. This paper presents the case of an HIV-infected patient who delayed the necessary treatment due to stigma and ultimately presented with AIDS. Through social support, however, he was able to overcome his internalized stigma; he was finally willing to start on antiretroviral treatment (ART). This case report addresses the effect of stigma on and the role of social support in the management of an individual with HIV.